Statements on Open Science for Sustainable Development Goals - Chew, Boon-How; Maxwell, Lauren; Anyiam, Felix Emeka; Menouni, Aziza; Kurniawan, Tonni Agustiono; Dimobe, Kangbéni; Sharma, Til Prasad Pangali; Ali, Gomaa A. M.; Shah, Ram Devi Tachamo; Saleem, Rabia; Mashroofa, Mohamed Majeed; Nasr, Maha; et al. (Ubiquity Press, 2024)
This article attempts to practicalise Open Science (OS) to promote ideas and enhance efforts for the Sustainable Development Goals (SDGs). It delineates General Statements (n = 20) as guiding beacons and the Specific Statements (n = 70) that act as precision tools in OS orientated policymaking, research, innovations, and public engagement, and access to scientific knowledge. The authors hope to draw kindled and educated attention to OS besides underscoring the need for unbiased, inclusive, and diligent execution of the SDGs. By adopting these Statements accordingly and in appropriate stages within national strategies and ensuring transparent reporting of the progress, the authors envision a transformed world by 2030. With this appeal, scientific endeavours could be more effectively directed and optimised with OS, significantly advancing progress toward the SDGs.